The infectivity of progeny adenovirus in the presence of neutralizing antibody. (12th April 2021) - Hirai, Takamasa; Sato, Anna; Koizumi, Naoya; Kurioka, Yoh; Suzuki, Yui; Kano, Junpei; Yamakawa, Makie; Nomura, Tetsuya; Fujii, Makiko; Sakurai, Fuminori; Mizuguchi, Hiroyuki; Watanabe, Yoshiteru; et al.
Abstract : Human adenoviruses (Ads), common pathogens that cause upper respiratory and gastrointestinal infections, are blocked by neutralizing antibodies (nAbs). However, Ads are not fully eliminated even in hosts with nAbs. In this study, we assessed the infectivity of progeny Ad serotype 5 (Ad5) in the presence of nAb. The infectivity of Ad5 was evaluated according to the expression of the Ad genome and reporter gene. Infection by wild-type Ad5 and Ad5 vector continued to increase until 3 days after infection even in the presence of nAb. We established an assay for determining the infection levels of progeny Ad5 using a sorting system with magnetic beads and observed little difference in progeny Ad5 counts in the presence and absence of nAb 1 day after infection. Moreover, progeny Ad5 in the presence of nAb more effectively infected coxsackievirus and adenovirus receptor (CAR)-positive cells than CAR-negative cells. We investigated the function of fiber proteins, which are the binding partners of CAR, during secondary infection, observing that fibre proteins spread from infected cells to adjacent cells in a CAR-dependent manner. In conclusion, this study revealed that progeny Ad5 could infect cells even in the presence of nAb, differing from the common features of the Ad5 infection cycle. Our findings may be useful for developing new therapeutic agents against Ad infection.